GW170817: implications for the local kilonova rate and for surveys from ground-based facilities. Issue 4 (18th September 2018) - Della Valle, M; Guetta, D; Cappellaro, E; Amati, L; Botticella, M T; Branchesi, M; Brocato, E; Izzo, L; Perez-Torres, M A; Stratta, G
ABSTRACT: We compute the local rate of events similar to GRB 170817A, which has been recently found to be associated with a kilonova (KN) outburst. Our analysis finds an observed rate of such events of $R_{\rm KN}\sim 352^{+810}_{-281}$  Gpc −3  yr −1 . After comparing at their face values this density of sGRB outbursts with the much higher density of binary neutron star (BNS) mergers of 1540$^{+3200}_{-1220}$  Gpc −3  yr −1, estimated by LIGO–Virgo collaboration, one can conclude, admittedly with large uncertainty that either only a minor fraction of BNS mergers produces short gamma-ray bursts (sGRB)/KN events or the sGRBs associated with BNS mergers are beamed and observable under viewing angles as large as θ ≲ 40°. Finally, we provide preliminary estimates of the number of sGRB/KN events detected by future surveys carried out with present/future ground-based/space facilities, such as LSST, VST, ZTF, SKA, and THESEUS.